ИНТЕГРИРОВАНИЕ МОДИФИЦИРОВАННОГО УРАВНЕНИЯ КОРТЕВЕГА-ДЕ ФРИЗА С НАГРУЖЕННЫМ ЧЛЕНОМ И ИСТОЧНИКОМ В ВИДЕ СУММЫ - Алланазарова, Т.Ж. (SCIENCE and SOCIETY, 2021)
This paper considers the method of the inverse spectral problem for integrating the modified Korteweg-de Vries equation (mKdV) with a loaded term and a source in the form of a sum in the class of infinite-gap periodic functions.
Keywords: Modified Korteweg-de Vries equations; Dirac operator; spectral data; inverse spectral problem; Dubrovin system of equations; trace formulas